Perancangan Sistem pemantau Luminer penerangan jalan Umum Tenaga Surya - Khe, Kelvin (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
Solar energy for public street lighting exemplifies the implementation of renewable energy on a city-wide scale, addressing environmental goals and enhancing energy efficiency. Solar panels capture sunlight, storing it in batteries to illuminate streets at night. Panel efficiency is influenced by sunlight intensity, directly impacting power production. Coupled with batteries, these systems undergo managed charging and discharging cycles for durability. Maintaining battery voltage within limits is crucial—preventing overcharging safeguards against degradation, while careful discharging avoids falling below specified levels. A solar charge controller module is essential for regulating these processes. Monitoring involves an INA219 sensor-based device communicating with the ESP32 microcontroller. The ESP32 transmits readings to a MySQL database server. During charging or sunlight exposure, the system reports solar panel and battery data. Conversely, at sunset, it relays battery discharge voltage. MySQL-stored data is displayed on a web page for real-time monitoring, with graphical representations and tables, automating and modernizing monitoring practices. System testing reveals minimal differences in INA219 sensor values compared to a Fluke multimeter. Accurate data transmission occurs every 5 minutes, and lamp status is trackable via lamp current. This integrated system highlights solar energy's viability for public infrastructure, fostering sustainability and efficiency in urban settings.